Fortitude in Wordsworth s poems 'Michael' Resolution and Independence and 'The thorn' (Journal of the College of Education for Women, 2019)
William Wordsworth is known as a poet of Nature but he aspired to be aphilosophical poet , whose major subject is man, " speaking to men in the language ofmen. " This aspiration is born inside him as he realizes the necessity to discussessential human issues as part of his duty as a didactic poet. Fortitude is among the themes that he tackles to teach man how to show courage against obstacles and impediments and live happily. The study sheds light on this theme in three of his major poems. In each one the sufferer shows fortitude because it is part of his aim to achieve continuity in life as in " Michael",or because it is part of his firmness of mind as in " Resolution and Independence "or because it is a necessity of existence as in " The Thorn"